Paradigma Hukum Berkeadilan Dalam Hak Kekayaan Intelektual Komunal - Fathoni Fathoni (Jurnal Cita Hukum, 2014)
Abstract: The Paradigm of Legal Justice in the Communal Intellectual property Rights. Law and justice is a synthesis therefore inseparable. Basically, our society doesn’t recognize what is called as conflict. Conflict has been introduced by the Globalization. The regime of Intellectual property Rights was born as the effect of the free trade that adopts the equality. All the parties are the gladiator that needs to be survives in the battle (survival for the fittest). On the contrary, the traditional society doesn’t pay attention on the economic values of the culture. However, they are forced to compete in the Intellectual Property Rights battle, especially the Property Rights. This article will elaborate the law enforcement with the justice approach at the Intellectual property Conflict taken place in the Society.\Abstrak: Paradigma Hukum Berkeadilan Dalam Hak Kekayaan Intelektual Komunal. Hukum dan keadilan adalah sebuah sintesis, sehingga tidak\ terpisahkan. Pada dasarnya masyarakat Indonesia tidak mengenal konflik. Perkembangan global dalam penerapan hukum yang telah memperkenalkan kosakata “konflik” ke masyarakat Indonesia. Regim Hak Kekayaan Intelektual (HKI), misalnya, yang lahir dari perdagangan bebas tentu tidak akan jauh dari prinsip-prinsip perdagangan bebas yang menuntut persamaan. Semua pihak dianggap sebagai "gladiator" yang harus mampu bertahan dalam pertarungan (survival for the fittest). Dalam kompetisi macam ini, masyarakat tradisional yang tidak begitu mempedulikan nilai ekonomis dari suatu kebudayaan. Namunbegitu mereka, “dipaksa” bertarung dalam potensi konflik HKI, terutama hak cipta. Tulisan ini mengelaborasi pendekatan penegakan hukum yang berorientasi keadilan dalam konflik HKI yang berpotensi muncul. DOI: 10.15408/jch.v1i2.1469